2016
DOI: 10.1111/nph.14024
|View full text |Cite
|
Sign up to set email alerts
|

Organ specificity in the plant circadian system is explained by different light inputs to the shoot and root clocks

Abstract: Summary Circadian clocks allow the temporal compartmentalization of biological processes. In Arabidopsis, circadian rhythms display organ specificity but the underlying molecular causes have not been identified. We investigated the mechanisms responsible for the similarities and differences between the clocks of mature shoots and roots in constant conditions and in light : dark cycles.We developed an imaging system to monitor clock gene expression in shoots and light‐ or dark‐grown roots, modified a recent mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(154 citation statements)
references
References 43 publications
13
129
0
12
Order By: Relevance
“…In addition, micrografting experiments demonstrated that the clock in the shoot apex can affect circadian rhythms in root tissues, although the actual nature of the systemic signaling component for rhythm coupling remains unknown . It is noteworthy that mathematical modeling suggests that the difference in clock properties between the shoot and root can be explained by light sensitivity of clock entrainment in each tissue (Bordage et al, 2016). Supporting this idea, tissue-specific clock properties, such as phase variation in clock genes, or different sensitivity to temperature signals, has been reported in intact Arabidopsis plants (Thain et al, 2002;Michael et al, 2003;Yakir et al, 2011).…”
Section: Tissue Specificity In Clock Functionmentioning
confidence: 59%
“…In addition, micrografting experiments demonstrated that the clock in the shoot apex can affect circadian rhythms in root tissues, although the actual nature of the systemic signaling component for rhythm coupling remains unknown . It is noteworthy that mathematical modeling suggests that the difference in clock properties between the shoot and root can be explained by light sensitivity of clock entrainment in each tissue (Bordage et al, 2016). Supporting this idea, tissue-specific clock properties, such as phase variation in clock genes, or different sensitivity to temperature signals, has been reported in intact Arabidopsis plants (Thain et al, 2002;Michael et al, 2003;Yakir et al, 2011).…”
Section: Tissue Specificity In Clock Functionmentioning
confidence: 59%
“…Plant cells act as self-sustained oscillators, with their own circadian clocks that regulate interactions with surrounding cells. Phase waves in leaves and roots (Fukuda et al, 2007;Wenden et al, 2012;Ukai et al, 2012;Fukuda et al, 2012), differences in inherent periods between tissues (Endo et al, 2014;Takahashi et al, 2015;Bordage et al, 2016), and spatiotemporal analytical data (Fukuda et al, 2007;James et al, 2008;Wenden et al, 2012;Fukuda et al, 2013) suggest that the cellular oscillator network involves nonlinear phenomena. It was also reported that growth and developmental processes in roots exhibit marked spatiotemporal patterns, such as striped waves resulting from strong phase resetting in the elongation-differentiation (ED) region of the root tip.…”
Section: Introductionmentioning
confidence: 99%
“…A novidade neste estudo foi dissecar os diferentes órgãos e detectar em qual estava a dominância de expressão dos genes do oscilador central, especulando sobre a possibilidade de uma sinalização de longa distância sincronizar o funcionamento dos relógios nos órgãos afastados do meristema apical (Takahashi et al, 2015). Embora tenha sido sugerido que o sinal sincronizador entre órgãos seja um metabólito da fotossíntese (James et al, 2008;Haydon et al, 2013;Takahashi et al, 2015), há evidências de que a luz possa ser percebida pelos órgãos e ser o elemento sincronizador entre os relógios dos órgãos de Arabidopsis (Bordage et al, 2016).…”
Section: O Relógio Biológico Das Plantasunclassified
“…Ou talvez a luz possa ser o fator de sinalização neste caso. Um estudo recente mostrou que em Arabidopsis, a raiz exposta à luz de baixa intensidade é percebida pelo oscilador deste órgão, regulando-o de forma semelhante à exposição a açúcar (Takahashi et al, 2015;Bordage et al, 2016).…”
Section: Expressão Dos Transcritos Para Os Genes Do Relógio Biológicounclassified
See 1 more Smart Citation